Moral and Ethical Crisis: The Impact of Lack of Implementation of Pancasila Values - Isna Aulia Adzani; Rahma Putri Wibowo; Shofia Lutfi Dzulfahmi; Rawanoko, Endrise Septina (Academic Solution Publisher, 2024)
Ethics and morals are very important in life, especially in the face of decline in the younger generation. This moral crisis is influenced by family, school, culture, and the rapid development of technology. Moral decline can hurt individuals and society. Based on a literature studies from several articles (2021-2024), the implementation of Pancasila values as moral education is very relevant. In the technological era, the moral crisis is getting worse, as seen from the many cases of deviation among the nation's children. Pancasila-based moral education can shape characters who are independent, responsible, and understand moral values. The implementation of Pancasila also prevents the degradation of the nation's character due to globalization. This research emphasizes the importance of Pancasila-based character education to build ethics and morals for the progress of Indonesia.